The Influence of Chronic Exposure to Antipsychotic Medications on Brain Size before and after Tissue Fixation: A Comparison of Haloperidol and Olanzapine in Macaque Monkeys - Dorph-Petersen, Karl-Anton; Pierri, Joseph N; Perel, James M; Sun, Zhuoxin; Sampson, Allan R; Lewis, David A (Neuropsychopharmacology (New York, N.Y.), 2005)
It is unclear to what degree antipsychotic therapy confounds longitudinal imaging studies and post-mortem studies of subjects with schizophrenia. To investigate this problem, we developed a non-human primate model of chronic antipsychotic exposure. Three groups of six macaque monkeys each were exposed to oral haloperidol, olanzapine or sham for a 17-27 month period. The resulting plasma drug levels were comparable to those seen in subjects with schizophrenia treated with these medications. After the exposure, we observed an 8-11% reduction in mean fresh brain weights as well as left cerebrum fresh weights and volumes in both drug-treated groups compared to sham animals. The differences were observed across all major brain regions (frontal, parietal, temporal, occipital, and cerebellum), but appeared most robust in the frontal and parietal regions. Stereological analysis of the parietal region using Cavalieri's principle revealed similar volume reductions in both gray and white matter. In addition, we assessed the subsequent tissue shrinkage due to standard histological processing and found no evidence of differential shrinkage due to drug exposure. However, we observed a pronounced general shrinkage effect of approximately 20% and a highly significant variation in shrinkage across brain regions. In conclusion, chronic exposure of non-human primates to antipsychotics was associated with reduced brain volume. Antipsychotic medication may confound post-mortem studies and longitudinal imaging studies of subjects with schizophrenia that depend upon volumetric measures.